SELF-EFFICACY AS A PROTECTIVE FACTOR IN MENTAL HEALTH: INSIGHTS FROM AN EARLY ADULTHOOD PERSPECTIVE - Kumar, Mahendra; Singh, Ankita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Self-efficacy is an important protective factor for mental health in early adulthood, especially during transitional life phases with increased sensitivity to stress and inter-role conflicts. Drawing on Bandura's social cognitive theory, this study synthesises existing data to investigate how self-efficacy promotes psychological resilience, coping mechanisms, and mental well-being throughout early adulthood, with a particular emphasis on gender-specific experiences. Empirical research shows that stronger self-efficacy is connected with lower stress, better family functioning, and better coping, particularly among women juggling career and household commitments. The review also emphasises the moderating impacts of familial environment, cultural context, and professional position, emphasising how self-efficacy interacts with other social variables. Future research implications include developing targeted treatments, addressing structural hurdles, verifying cross-cultural models, and applying longitudinal approaches. Overall, developing self-efficacy emerges as a critical approach for promoting mental health resilience in young people navigating complicated psychosocial environments.